PERSEPSI SISWA KELAS X2 MA DARUL HIKMAH PEKANBARU TERHADAP PENERAPAN MODEL PEMBELAJARAN IQRO’ PADA MATA PELAJARAN BIOLOGI TAHUN AJARAN 2014/2015 - Nurasni '; Darmawati '; Yustini ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : It has conducted study that aimed to determine students 'perception toward Iqro Learning model implementation in biology subject because students’ condition still did not show a good perception towards learning biology and teachers have never implement a model that integrates biological material with a religious boarding school. This study was conducted in MA Darul Hikmah Pekanbaru from April to May 2015 on ecosystem subject. This research was descriptive. The population of this research was all students of class X MA Darul Hikmah Pekanbaru, and the samples were students of class X2 Pekanbaru MA Darul Hikmah School Year 2014/2015 which consisted of 30 female students. Parameter that used was students’ perception with five indicators, namely attention, expectations, needs, system values, and personality type. Instruments that used was enclosed questionnaire. Data were analyzed by using a calculation based on a graduated scale. The results showed that students’ perceptions of class X2 Pekanbaru MA Darul Hikmah School Year 2014/2015 against Iqro learning model' on the subjects of Biology at attention indicators categorized good with a mean of 4.4, the expectations indicator categorized good with a mean of 4.28, the indicator needs categorized excellent with a mean of 4.85, on value system of indicators categorized excellent with a mean of 5.11 and the personality type indicator categorized very well with the average of 5.44. From the results of this study concluded that students’ perception of Class X2 MA Darul Hikmah pekanbaru t toward Iqro Learning model implementation in biology subject Academic Year 2014/2015 in excellent category once since the acquisition of the overall mean score was 4.82. Keywords: Students’ perceptions, iqro learning model , MA Darul Hikmah Pekanbaru